Investigating the Formation of Metal-Superoxides: Iron and Nickel Complexes Based on a 2,6-Pyridinedicarboxamide Ligand System - Nelis, Daniel (Trinity College Dublin, School of Chemistry, 2020)
Metal-superoxide intermediates have been proposed to be key active intermediates in the catalytic cycles of a wealth of oxygen-activating enzymes in biology. Synthetically, many examples of such intermediates have been spectroscopically characterised of which Fe and Cu containing superoxide complexes have been most studied. However, there exists only a small number of reported Ni-superoxide complexes. This work details the synthesis of two FeII complexes based on the N,N-bis(2,6-diisopropylphenyl)-2,6-pyridinedicarboxamide ligand framework of which one of these complexes, with an Fe2(OH)2 core has been structurally characterised. The structure of this complex showed it to be a dinuclear complex wherein the ligand bound via the oxygen atoms to a metal, rather through the more conventional amidic nitrogen atoms. The reactivity of a previously reported nickel complex, of the same ligand system, with potassium superoxide has also been investigated and lead to the formation of two NiII complexes, a NiII-hydroxide complex, as well as a NiII complex wherein the coordinated ligand has undergone insertion of an oxygen atom into one of its C-H bonds. The latter has been proposed to form through a heterolytic electrophilic hydrogen atom abstraction reaction of a NiII-superoxide intermediate followed by rebound of a hydroxyl radical to form the hydroxylated ligand. Following post-reaction acidified workup, the position of hydroxylation was determined to be at the methine iPr position. This reactivity has been proposed to follow a similar route as the initial steps for the enzyme Isopenicillin N Synthase, a non-heme iron enzyme used in the synthesis of penicillin. The isolation of metal-oxygen adducts both in biology and in synthetic systems has most often required the use of cryogenic temperatures. Many of these species decay within seconds or minutes of their formation. Thus, X-ray Absorption Spectroscopy is a spectroscopic technique which has been used to give electronic and structural information of frozen solutions of these unstable intermediates. This thesis concludes with the study of three such intermediates by X-ray absorption near-edge spectroscopy and extended X-ray absorption fine structure analysis. This allowed the oxidation state of each metal site to be identified as well as giving insights into the electronic symmetry surrounding each metal site and the metal-ligand bond distances.
Keywords: Bioinorganic; Superoxide; Metal complex; X-ray absorption spectroscopy; Catalytic cycle